The effect of vermicompost treatments on yield and yield components of peanut (Arachis hypogaea L.) (Bioagro, 2023)
This study was conducted to determine the effects of vermicompost treatments on yield and yield components of peanut (Arachis hypogaea L.) under Osmaniye ecological conditions, in Türkiye, in 2020-2021. It was designed according a complete randomized block with three replications. The NC-7 peanut variety was treated with eight different treatments of vermicompost plus a control. The treatments T1 through T4 included soil and leaves applications at different plant development stages, and treatments T5 through T8 were similar to the previous four but included only application to leaves. The number of pods per plant, pod weight per plant, 100-pod and seed weight, shelling percentage, first quality pod ratio, first quality pod weight ratio, protein content, and pod yield were determined. The number of pods per plant varied between 23.3 (control) and 33.4 (T1). The lowest pod weight per plant was 37.7 g in control treatment, and the  highest  in  T1  (51.4 g).  Pod yield  was  between  3579 kg∙ha-1  (control)  and  4873 kg∙ha-1 in T1. The 100-pod weight was the lowest from the control treatment (208.4 g) and the highest from the T6 treatment (254.2 g); the weight of 100 seeds was minimum in the control treatment with 88.5 g and maximum in T5, with 102.3 g. The protein content varied between 24.11% (control) and 26.01% (T5). These results indicate that under the ecological conditions of Osmaniye province, there  is a significant effect of vermicompost on most productive and quality variables of peanut.
Keywords: Number of pods; Osmaniye; pod weight; protein content